Dreaming tongues. (6th January 2011) - Munro, Stuart
If art, technology and landscape were thought of in the same sentence and the result of this cocktail a relationship between body and landscape, then one by-product would be 'place' becoming 'placeless'. The active agent in all of this would be complexity. Not complexity in a random sense where things come together in a dense and 'complex' way but in a coming together or pulling apart that is experienced by a collection of objects and world-views formed from the creation of artwork, architectural intervention and technological convenience. Through the following journey from city to island I give a snapshot of the sorts of complex and diverse pieces that work, at times together and at other times apart, to represent a landscape, urban and rural, that continuously reshapes itself through a response to art, commerce, science, politics and much more. The narration is shown in italics throughout. Parallel to this is a sequence of work, in its early stages, that pulls together some of these interests and observations where the liquid, the visceral, the actual and the virtual all mediate between two distinct locations one in England and one in Japan coming together in a developing photographic sequence